Rice biofortification: breeding and genomic approaches for genetic enhancement of grain zinc and iron contents - Senguttuvel, P.; G, Padmavathi; C, Jasmine; D, Sanjeeva Rao; CN, Neeraja; V, Jaldhani; P, Beulah; R, Gobinath; J, Aravind Kumar; SV, Sai Prasad; LV, Subba Rao; AS, Hariprasad; et al. (Frontiers in Plant Science, 2023)
Rice is a highly consumed staple cereal cultivated predominantly in Asian countries, which share 90% of global rice production. Rice is a primary calorie provider for more than 3.5 billion people across the world. Preference and consumption of polished rice have increased manifold, which resulted in the loss of inherent nutrition. Prevalence of micronutrient deficiencies (Zn and Fe) are major human health challenge in the 21st century. Biofortification of staples is a sustainable approach to alleviate malnutrition. Globally, significant progress has been made in rice for enhancing grain Zn, Fe and protein. To date, 37 biofortified Zn/Fe, protein and Pro-Vitamin A rich rice varieties are available for commercial cultivation (16 from India and 21 from the rest of the world; Fe > 10 mg.kg-1; Zn > 24 mg.kg-1, protein > 10% in polished rice as India Target; while Zn > 28 mg.kg-1 in polished rice as International Target). However, understanding the micronutrient genetics, mechanisms of uptake, translocation and bioavailability are the prime areas that need to be strengthened. The successful development of these lines through integrated-genomic technologies can accelerate in deployment and scaling in future breeding programs to address the key challenges of malnutrition and hidden hunger.